WUJUD WARNA LOKAL LAMALERA DALAM NOVEL LAMAFA KARYA FINCE BATAONA (Universitas Negeri Semarang, 2023)
The tradition of whaling in Lamalera is a tradition that the people of the Lamalera fishing village routinely carry out. Fince Bataona wrote about this whaling tradition, emphasising the stabber in his novel Lamafa. This study aims to describe the shape of the local Lamalera colour contained in the Lamafa novel. This study uses qualitative descriptive research with an anthropological literary approach. The source of this research is the novel Lamafa by Fince Bataona. The research data is in the form of sentences or paragraph fragments containing the local colour of Lamalera. Data collection was carried out using reading, note-taking, and coding techniques. In contrast, data analysis used content analysis techniques, namely connecting the novel's contents with the theory of literary anthropology. The results of the analysis show that the Lamafa novel contains a form of Lamalera's local colour, namely: (1) social system or social status, (2) whaling tools or equipment, (3) art, (4) religious or belief systems, (5) greetings, and (6) the name of the animal.